Secretion Rates of Human Nasal Submucosal Glands from Patients with Chronic Rhinosinusitis or Cystic Fibrosis. Issue 5 (September 2015) - Jeong, Jin Hyeok; Hwang, Peter H.; Cho, Do-Yeon; Joo, Nam Soo; Wine, Jeffrey J.
Background: A majority of patients with cystic fibrosis (CF) have chronic rhinosinusitis (CRS) and/or nasal polyps, both of which may be secondary to reduced fluid secretion from nasal submucosal glands. Objective: To determine whether decreased fluid secretion from nasal submucosal glands also occurs in patients without CF and with CRS. Methods: Inferior turbinates of the nasal cavity were harvested from controls, subjects with CRS, and subjects with CF (n = 5–7 per group). The secretion rates of the nasal submucosal glands of the three groups in response to carbachol and forskolin were measured by using time lapse digital imaging of mucus bubbles from single glands as they formed on the mucosal surface under oil. Results: Carbachol-stimulated secretion rates were the following: controls, 1670 ± 381 pl-min −1 -gland −1 ; CRS, 965 ± 440 pl-min −1 -gland −1 ; and CF, 933 ± 588 pl-min −1 -gland −1 (p = 0.23, Kruskal-Wallis test). Forskolin-stimulated secretion rates were the following: controls, 229 ± 14 pl-min −1 -gland −1 ; CRS, 154 ± 48 pl-min −1 -gland −1 ; and CF, 22 ± 15 pl-min −1 -gland −1 (p = 0.008, Kruskal-Wallis test). The ratio of the average secretion rate induced by forskolin to that induced by carbachol was 13.7% in the controls, and 15.9% in CRS and 2.3% in CF groups. Conclusion: The only significant difference in this small study was decreased forskolin-stimulated secretion in subjects with CF relative to the other subjects. However, there was a trend toward reduced carbachol-stimulated secretion rates in subjects with CRS and with and without CF relative to controls. Additional studies are needed to determine if nasal submucosal gland hyposecretion occurs in CRS either as a contributor to or as a consequence of CRS pathogenesis.